Analisis tes ulangan harian pelajaran matematika kelas 5 - Kurniawan, Fuji; Pane, Putra Sitorus; Muhdi, Ridha (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Item analysis is conducted to improve the quality of test items through the revision and correction of ineffective questions, as well as to obtain diagnostic information about students' understanding of the material that has been taught. This study uses the Rasch model to analyze the quality of 10 test items and the abilities of fifth-grade students at SDN 1 Syaemtaelirae Baeyue. The purpose of this research is to evaluate the quality of the test items and to assess the abilities of 30 students at the school. This research is an evaluative study with a descriptive qualitative approach. The results indicate that all test items analyzed are valid and reliable. Out of the 10 items analyzed, 4 items (38.5%) are categorized as easy, 4 items (38.5%) as moderate, and 2 items (23.1%) as difficult. Based on this analysis, the test items used are of good quality because they effectively measure students' abilities and show variation in difficulty levels. Additionally, the students' abilities at SDN 1 Syaemtaelirae Baeyue are diverse, with 73.3% of students able to answer questions in the easy category, 46.7% able to answer questions in the moderate category, and 16.7% able to answer questions in the difficult category.